Las Patronas, Clientelism, and Care - Bruzzone, Mario (My University, 2012)
In La Patrona you learn by sound which direction the train is traveling--but not in the obvious way. The trains' oatmealy engine noise gets easily confused with the far-off bounce and clatter of sugarcane trucks wending through newly-cut fields. Train whistles echo off green hills, and the rumbles of a train churlishly moving south and one exhaustedly rumbling north may both suggest movement in the same direction. Sometimes the trains surprise you, and sometimes you think you hear them coming but they never appear. There is talk that clouds; or winter; or whether the Pico de Orizaba is visible can tell you how distant you might hear the trains. Women are said to be worse than men at knowing the direction of travel, and all teenagers especially inattentive, but anyone can learn to hear. There are many other papers to be written on, and with, the Patronas. The papers here are intended not as a comprehensive account but as two of the many ways of making sense of my time in La Patrona. They are not, or not yet, the type of action the Patronas want, but they are not meant to be. Their audience is different, and they are necessarily incomplete. They are partial, in both senses of the word--but life, as feminist theorists remind us, exists no other way.
Includes color photographs, figures, maps and bibliography.
Keywords: Care; Clientelism; La Patrona; Patronas